Mechanical Test of Brick with Addition of Sugarcane Bagasse Ash - Sawitri, Indah (Universitas Islam Negeri Sumatera Utara Medan, 2022)
Research has been done on the mechanical test of brick with the addition of bagasse ash. In this study, the tested bricks tested were compressive strength and fracture strength. The purpose of this study was to determine the effect of adding bagasse ash to the mechanical properties of bricks. The variation of the percentage of bagasse ash, cement, and sand is 0% : 30% : 70% , 5% : 25% : 70%, 10% : 20% : 70%, 15% : 15% : 70%, 20% : 10% : 70% and used FAS (Water Cement Factor) of 0.5 in all variations. The addition of bagasse ash as a substitute for cement has a significant effect on the characteristics of the bricks. With the addition of bagasse ash in a mixed variation of 5 – 20% causes the compressive strength value to decrease. Meanwhile, the fracture strength increased in the mixed variation of 5-10% and decreased in the mixed variation of 15-20%. The most optimal composition of the mixture of bagasse ash, cement, and sand is at a mixture variation of 5% for compressive strength testing and fracture strength testing because it meets SNI 03-0348-1989 standards. While the other mixture variations are not optimal.